Local resection versus radical resection after neoadjuvant chemoradiotherapy for patients with locally advanced rectal cancer: a propensity-score matched cohort analysis - Guancong Wang; Kaiyuan Yao; Yugang Yang; Hongying Chen; Zihan Tang; Jiahong Ye; Muhai Fu; Xiajuan Xue; Qiyuan Shen; Haiwen Tang; Yincong Guo; Ying Huang (BMC Gastroenterology, 2023)
Abstract Background We aimed to address the shortage of evidence regarding the safety of the local resection approach by comparing long-term oncological outcomes between patients managed by local resection and those who underwent radical resection. Methods This was a propensity-score matched cohort analysis study that included patients of all ages diagnosed with locally advanced rectal cancer (LARC) who had received neoadjuvant chemoradiotherapy (nCRT) at the Fujian Medical University Union Hospital and Fujian Medical University Affiliated Zhangzhou Hospital, China, between Jan 10, 2011, to Dec 28, 2021. Partial patients with a significant downstage of the tumor were offered management with the local resection approach, and most of the rest were offered radical resection if eligible. Findings One thousand six hundred ninety-three patients underwent radical resection after nCRT, and another 60 patients performed local resection. The median follow-up times were 44.0 months (interquartile range = 4–107 months). After propensity-core matching (PSM), in the Kaplan–Meier curves, local resection (n = 56) or radical resection (n = 211) was not significantly associated with 1-, 3-, and 5-year cumulative incidence of overall survival (OS) (HR = 1.103, 95% CI: 0.372 ~ 3.266), disease-free survival (DFS) ((HR = 0.972, 95% CI: 0.401 ~ 2.359), local recurrence (HR = 1.044, 95% CI: 0.225 ~ 4.847), and distant metastasis (HR = 0.818, 95% CI: 0.280 ~ 2.387) (all log-rank P > 0.05). Similarly, multivariate Cox regression analysis indicates that local excision still was not an independent risk factor for OS (HR = 0.863, 95% CI: 0.267 ~ 2.785, P = 0.805) and DFS (HR = 0.885, 95% CI: 0.353 ~ 2.215, p = 0.794). Conclusion Local resection can be a management option in selected patients with middle-low rectal cancer after nCRT for LARC and without loss of oncological safety at five years.